PENGARUH STRESS DI LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. RADIO WAHANA INFORMASI GEMILANG - EDWIN SANTOSO, WIGO (Jurnal Ilmu Manajemen (JIM), 2019)
This study aims to examine the effect of independent variables (stress and physical work environment) on employee performance at PT. Radio Wahana Informasi Gemilang Surabaya.Data obtained from the results of questionnaires and interviews. The sample in this study were 54 respondents who were taken by the Slovin formula sample method. Data collection techniques used are questionnaire techniques that are distributed directly to respondents in this case are employees of PT. Radio Wahana Informasi Gemilang Surabaya. Data analysis techniques using multiple linear regression analysis. This study uses reliability, validity and classical assumption techniques. The results of this study indicate that stress independent variables have no effect and the physical work environment has a positive effect on employee performance Keywords: employee performance; job stress; physical work environment.